Análise das propriedades estáticas e dinâmicas das espécies de Bambu bambusa tuldoides e Phyllostachys aurea - Vasata, Ana Claudia Dal Pra (2020)
Bamboo is a sustainable material, which as well as good mechanical properties, can narrow the waste generated by civil construction. This paper seeks to experimentally determine the static and dynamic properties of bamboo species Bambusa tuldoides (BT) and Phyllostachys aurea. Bamboo samples, with moisture content between 12% and 15%, were statically tested at bending, compression, and tensile parallel to the fibers. The elasticity modulus was determined for each test, and for the last two, the stress has been calculated. The dynamic properties such as natural frequency for the first mode of vibration, damping coefficient and dynamic elasticity modulus, were defined through free vibration test. BT species showed a mean value of compressive stress of 10.14% lower than PA species, however, for tensile stress, the first one obtained a mean value of tensile stress of 21.47% higher than the second one. As for the compression, tensile and bending elasticity modulus, BT species obtained higher values in all tests compared to PA species, showing a difference of 9.7%, 0.65% and 26.8%, respectively. For the dynamic elasticity modulus, BT species showed a mean value of 36.33% higher than PA species. As for the damping coefficient, PA species showed the highest values, with a difference of 53.43% in relation to BT species. Therefore, the potential of using bamboo in civil construction as a structural and sustainable material is remarkable.reas for the PA species the results were respectively near to 3.35%, 3,68 GPa and 1.38 GPa.